2018
DOI: 10.1007/s10047-018-1043-4
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and self-care correlates before and after implantation of a left-ventricular assist device (LVAD)

Abstract: The impact of sleep on LVAD patients' self-care behaviors is unknown. This study examined the patterns and changes of patients sleep quality (SQ), daytime sleepiness (DS), instrumental activities of daily living (IADL), and self-care capability (SCC) before and after LVAD. In addition, the relationships among these variables were explored. This observational study consisted of 38 subjects from two VAD Centers in Michigan. The subjects completed self-reported demographics and psychometrically sound SQ, DS, IADL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Previous research on self-care has mainly been conducted in patient samples (with reference to specific diseases) or caregivers (Casida et al, 2018;Shapiro et al, 2007). Nevertheless, especially in periods of crisis self-care behaviors should be investigated in the whole population as they might be useful for everyone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on self-care has mainly been conducted in patient samples (with reference to specific diseases) or caregivers (Casida et al, 2018;Shapiro et al, 2007). Nevertheless, especially in periods of crisis self-care behaviors should be investigated in the whole population as they might be useful for everyone.…”
Section: Introductionmentioning
confidence: 99%
“…Further, sleep has mostly been considered as a predictor for self-care behavior (e.g. Casida et al, 2018). A study by Di Benedetto et al (2019) found healthy self-care behaviors went along with good sleep quality, suggesting that healthy self-care behavior might also promote good sleep.…”
Section: Introductionmentioning
confidence: 99%
“…This is relevant, because short sleep duration and poor sleep are associated with coronary heart disease, metabolic disorders (Lao et al, 2018), and depressive symptoms (Lippman et al, 2017). Poor sleep quality has been reported in people with abdominal LVADs, when often results in worse performances in the activities of daily living (Casida et al, 2018). However, participants in this study reported an overall good sleep quality; as previously shown in people with the abdominal version of the device, this could be due to decreasing symptom burden and to improvements in patients’ adaptation to the LVAD (Casida et al, 2018).…”
Section: Discussionmentioning
confidence: 99%